Genetic patterns reveal differences between the invasion processes of common ragweed in urban and non-urban ecosystems - Siran Lu; Xiangyu Luo; Linwei Han; Jingyi Yang; Jing Jin; Jun Yang (Global Ecology and Conservation, 2022)
Invasive alien plant species (IAPS) in urban ecosystems can significantly impact ecosystems and human wellbeing. However, our knowledge on the IAPS in urban ecosystems are limited due to the small number of studies. In this study, we examined features of the invasion process of common ragweed (Ambrosia artemisiifolia L.) by using a comparative study approach and genetic population methods. We conducted field surveys in 19 prefecture-level cities in East China and collected samples of 37 urban and 18 non-urban populations in 16 cities. Using information from six microsatellite loci and two chloroplast spacers extracted from the samples, we tested hypotheses on the source, genetic diversity, and genetic patterns of urban populations of common ragweed. We found that urban populations of common ragweed had more modern and diverse invasion sources than that of non-urban populations. Also, urban populations had more complex genetic patterns than non-urban populations as we identified seven genetic clusters in urban populations and four genetic clusters in non-urban populations. Nevertheless, no significant difference was found between the genetic diversity of urban and non-urban populations. In addition, we observed a significant isolation by distance (IBD) pattern in non-urban populations (Mantel test, R2 =0.160, p-value=0.001) but not in urban populations (R2 =0.003, p-value=0.253). The patterns may be shaped by the long-distance dispersal of seeds of common ragweed in urban environments through human activities such as transportation. Our results contribute to a better understanding of the invasion process of IAPS in urban ecosystems.